1999
DOI: 10.1111/j.1469-7793.1999.555ac.x
|View full text |Cite
|
Sign up to set email alerts
|

A method for determining baroreflex‐mediated sympathetic and parasympathetic control of the heart in pregnant and non‐pregnant sheep

Abstract: A number of clinical and experimental studies have examined the effects of pregnancy on the cardiac baroreflex. The results obtained vary. For example, it has been reported that baroreflex sensitivity was decreased during pregnancy in women (Souma et al. 1983), in pregnant ewes (Ismay et al. 1979;Keller-Wood, 1995) and in pregnant rabbits (Cumbee et al. 1986). In other studies, however, it was found to be increased in women (Leduc et al. 1991), or unchanged in pregnant sheep (Magness & Rosenfeld, 1988). We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
25
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
3
25
0
Order By: Relevance
“…However, it should be noted that vagal withdrawal is likely to induce only a modest rise in heart rate in sheep. Previous studies both from our laboratory (unpublished data) and from the literature (Hays & Webster 1971, Lumbers & Yu 1999 show that i.v. atropine or vagal section increases heart rate in sheep by w20-30 bpm with the maximum heart rates observed following withdrawal of vagal tone being 110-120 bpm.…”
Section: Discussionmentioning
confidence: 96%
“…However, it should be noted that vagal withdrawal is likely to induce only a modest rise in heart rate in sheep. Previous studies both from our laboratory (unpublished data) and from the literature (Hays & Webster 1971, Lumbers & Yu 1999 show that i.v. atropine or vagal section increases heart rate in sheep by w20-30 bpm with the maximum heart rates observed following withdrawal of vagal tone being 110-120 bpm.…”
Section: Discussionmentioning
confidence: 96%
“…In the adult the increase in heart rate in response to a decrease in blood pressure is rapid and is primarily due to withdrawal of vagal activity (12,25,34,50), although there is some evidence for a more significant role for the sympathetic nervous system (17) or a combination of the two systems (37,46,47). In the preterm fetus, the autonomic nervous system is still developing (2,31,48), and blockade of resting vagal activity at this gestational age does not significantly alter baseline HR (48).…”
Section: Discussionmentioning
confidence: 99%
“…11). However, appropriate baroreflex responses have been extensively documented with these agents in adult and nearterm fetal studies (25,39,54). In addition, the present studies were carried out between 24 and 72 h after the end of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cyclic variations in arterial blood pressure influence heart rate through the autonomically mediated baroreceptor reflex 14 . In a recent study on sheep it was shown that there is attenuation of baroreceptor mediated sympathetic effects on the maternal heart during pregnancy 16 . No differences in maternal heart rate variability were found between the two gestational age periods, suggesting that the growing fetus between 10 and 20 weeks of gestation does not influence maternal autonomic state.…”
Section: Discussionmentioning
confidence: 99%